Whole grain products in Brazil: the need for regulation to ensure nutritional benefits and prevent the misuse of marketing strategies - Giovanna Calixto Andrade; Laís Amaral Mais; Camila Zancheta Ricardo; Ana Clara Duran; Ana Paula Bortoletto Martins (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE This study aims to evaluate the use of "whole grains" claims in food products marketed in Brazil and evaluate the nutrient profile of these products. METHODS Data from 775 grain-based packaged foods collected in Brazil from April to July 2017 were analyzed. Based on the INFORMAS protocol for food labeling, the prevalence of packaged foods with "whole grains" claims was estimated. Information on the list of ingredients was analyzed to evaluate the presence and amount of whole or refined grains in six food groups. The nutrient profiles of the products with and without "whole grains" claims were compared using the Pan American Health Organization (PAHO) nutrient profile model. RESULTS The packages of about 19% of the evaluated products showed "whole grains" claims in their front panel. Of these, 35% lacked any whole grains among their top three ingredients. Breakfast cereals, granola bars, bread, cakes and other bakery products, cookies, and pasta had higher amounts of refined flour than whole grain ingredients in their compositions.We found 66% of products with "whole grains" claims were high in nutrients of concern according to PAHO's criteria. CONCLUSION Our results showed that over a third of the products in Brazil with "whole grains" claims lacked whole grains as one of their main ingredients. Most had a high content of nutrients associated with noncommunicable chronic disease risk factors, indicating the overestimation of their health benefits.